The Arab Spring and the Employability of Youth: Early evidence from Egypt - Irene Selwaness; Rania Roushdy (Global Labor Organization (GLO), 2017)
This paper investigates the school-to-work transition of young people from subsequent graduation cohorts between 2005 and 2012 in Egypt. The analysis compares the early employment outcomes of those who left school after the January 25th 2011 revolution to that of those who graduated before 2011. Using recent data from the 2014 Survey of Young People in Egypt (SYPE), we estimate the probability of transition to any first job within 18-month of finishing education and that of transitioning to a good quality job, controlling for the year of end of schooling. Preliminary findings show that while transitioning to a first job seemed not to be affected by the event of the 2011 revolution, young people experienced significantly lower chances to transition to good quality jobs.
Keywords: J13; J64; N35; 330; School-to-work transition; youth; survival-analysis; Egypt